Evaluating the Impact of a Futures-Oriented Organization. (December 2019) - Vataja, Katri; Dufva, Mikko; Parkkonen, Pinja
Foresight and futures work aim at imagining, rethinking, and setting conditions for systemic changes in the society. The societal change as a starting point of evaluation poses challenges to the traditional evaluation approaches. To analyze whether something has an impact on systemic changes, we need methods that consider the dynamics of the operating environment, the multi-actor perspective, and the long-time span of societal changes. In this article, we explore the design and methodological questions related to evaluating the impact of actors, which have set goals for societal impact of their futures work. Our case is based on the wide-scale evaluations of the Finnish Innovation Fund Sitra. In this article, we describe the process and thinking behind the evaluation of the futures work at Sitra and illustrate it with a case study of an evaluation of one of Sitra's impact goals. Based on our experience from this and other impact evaluations, we provide good practices and recommendations on how to evaluate futures work and foresight in a way that helps steer an organization's actions.